2014
DOI: 10.1177/0888406414558096
|View full text |Cite
|
Sign up to set email alerts
|

Views From the Trenches

Abstract: The current prevalence rates for autism spectrum disorder (ASD) coupled with the mandate to provide services to students with disabilities in inclusive classrooms warrants the need to examine the dynamics of inclusion for students with ASD. Focus groups were conducted with special and general educators at the elementary, middle, and high school levels to determine the needs of students with ASD in fully inclusive settings as well as teachers’ needs in facilitating their students’ success. The study was transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…The need for support reverberated throughout the study. Lack of sufficient support staff has been documented as a barrier to the implementation of EBPs for social skills (Able et al, 2015;Locke et al, 2015) Lack of emotional support has been alluded to in prior studies, such as the reference to a school's climate or culture impacting the implementation of EBPs or to feelings of burnout reported by staff working with students with ASD (Corona, Christodulu, & Rinaldi, 2017;Woodcock & Woolfson, 2019). In addition, inclusion has been linked to higher rates of teacher stress and burnout, particularly for those regular education teachers who have not had the benefit of the training that they special education counterparts have experienced (Boujut et al, 2016;Lindsay et al, 2013).…”
Section: Discussion/implications For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…The need for support reverberated throughout the study. Lack of sufficient support staff has been documented as a barrier to the implementation of EBPs for social skills (Able et al, 2015;Locke et al, 2015) Lack of emotional support has been alluded to in prior studies, such as the reference to a school's climate or culture impacting the implementation of EBPs or to feelings of burnout reported by staff working with students with ASD (Corona, Christodulu, & Rinaldi, 2017;Woodcock & Woolfson, 2019). In addition, inclusion has been linked to higher rates of teacher stress and burnout, particularly for those regular education teachers who have not had the benefit of the training that they special education counterparts have experienced (Boujut et al, 2016;Lindsay et al, 2013).…”
Section: Discussion/implications For Practicementioning
confidence: 99%
“…There is a critical lack of guidelines and training in teacher programs regarding the implementation of EBPs for autism (Lauderdale-Litten & Brennan, 2018;Scheeler, Budin, & Markelz, 2016). School staff have also reported that they do not have adequate support staff to facilitate EBPs for students (Able, Sreckovic, Schultz, Garwood, & Sherman, 2015;Locke et al, 2015). The lack of educator practice guidelines and training in teacher programs have contributed to the lack of implementation of appropriate interventions (Lauderdale-Litten & Brennan, 2018;Marder & Fraser, 2012).…”
Section: Evidence-based Practices For Social Skillsmentioning
confidence: 99%
“…And so I thought that was really successful and now he's doing broadcast at (the local community college). So that little thing where he was about to climb up on the A recent focus-group study of elementary through secondary teachers supports these reflections of the importance of self-advocacy (Able, Sreckovic, Schultz, Garwood, & Sherman 2015). Teachers in this study noted that students with Autism Spectrum Disorder need to be able to point out their own strengths and weaknesses because it can take teachers and peers time to figure out the more individualized traits on their own.…”
Section: Role Of Advocacymentioning
confidence: 58%
“…This study did not report the demographics of the categories of disabilities the teachers were referring to when they took the survey, so perhaps this need for specificity is more unique to the IEPs for students with Autism Spectrum Disorders. However, in a 2015 research study targeted specifically at general education teachers who have students with Autism Spectrum Disorder in their general education classrooms, the need to make IEPs more accessible and useful by outlining each students' characteristics and needs with corresponding accommodations needed was suggested by the teachers who participated in the study (Able, et al, 2015).…”
Section: Role Of Advocacymentioning
confidence: 99%
See 1 more Smart Citation